Pengaruh Hedonic Shopping Value, Shopping Lifestyle Dan Fashion Involvement Terhadap Impulse Buying Dengan Positive Emotion Sebagai Variabel Mediasi Pada pelanggan Shopee - Muhammad, Supriyanto; Rosdiana, Rosdiana; Ruray, Titiek Arafiani (Peneliti.net, 2025)
This study aims to determine the effect of hedonic shopping value, shopping lifestyle, and fashion involvement on impulse buying with positive emotion as a mediating variable among Shopee customers in the Kaiyasa Village community. This research uses a quantitative method. The population in this study is the community of Kaiyasa Village in Tidore Kepulauan City, consisting of 100 people.The results of the study show that hedonic shopping value does not have a positive and significant effect on impulse buying, as evidenced by the t-count value of 1.302 < t-table 1.660 with a significance level of 0.196 > 0.05. Shopping lifestyle does not have a positive and significant effect on impulse buying, as evidenced by the t-count value of 0.296 < t-table 1.660 with a significance level of 0.768 > 0.05.Fashion involvement has a positive and significant effect on impulse buying, as evidenced by the t-count value of 3.080 > t-table 1.660 with a significance level of 0.003 < 0.05. Positive emotion has a positive and significant effect on impulse buying, as evidenced by the t-count value of 2.641 > t-table 1.660 with a significance level of 0.010 < 0.05.Hedonic shopping value has a positive and significant effect on positive emotion, as evidenced by the t-count value of 2.181 > t-table 1.660 with a significance level of 0.032 < 0.05. Shopping lifestyle does not have a positive and significant effect on positive emotion, as evidenced by the t-count value of 0.702 < t-table 1.660 with a significance level of 0.484 > 0.05. Fashion involvement does not have a positive and significant effect on positive emotion, as evidenced by the t-count value of 0.969 < t-table 1.660 with a significance level of 0.335 > 0.05.Positive emotion is not able to mediate the effect of hedonic shopping value on impulse buying, as evidenced by the t-count value of 1.165 < t-table 1.660 with a significance level of 0.121 > 0.05. Positive emotion is not able to mediate the effect of shopping lifestyle on impulse buying, as evidenced by the t-count value of 0.293 < t-table 1.660 with a significance level of 0.384 > 0.05.Positive emotion is able to mediate the effect of fashion involvement on impulse buying, as evidenced by the t-count value of 2.004 > t-table 1.660 with a significance level of 0.022 < 0.05.